Red Yeast Rice for Hyperlipidemia: A Meta-Analysis of 15 High-Quality Randomized Controlled Trials - Li, Pengfan; Wang, Qi; Chen, Kanjun; Zou, Shihui; Shu, Shi; Lu, Chanchan; Wang, Shiyun; Jiang, Yunqin; Fan, Chunxiang; Luo, Yue (Frontiers in Pharmacology, 2022)
Background: RYR is a commonly used lipid-lowering dietary supplements in Asian and European countries, showing considerable benefits and low toxicity. This quantitative study aims to present high-quality evidence regarding the efficacy and safety of RYR in treating hyperlipidemia, in order to promote its clinical application. Methods: PubMed, embase, and Cochrane Central Register of Controlled Trials databases were systematically searched, and high-quality randomized controlled trials comparing RYR with non-RYR interventions were included. RevMan5.3 software was used to conduct the meta-analysis. Results: A total of 1,012 individuals participated in this study (481 in the experimental and 531 in the control group). In comparison to statins, RYR was more effective in lowering TG (MD, −19.90; 95% CI, −32.22 to −7.58; p = 0.002), comparable in lowering LDL-C and elevating HDL-C, and less effective in lowering TC (MD, 12.24; 95% CI, 2.19 to 22.29; p = 0.02). Compared with nutraceutical, RYR significantly reduced TC (MD, −17.80; 95% CI, −27.12 to −8.48; p = 0.0002) and LDL-C (MD, −14.40; 95% CI, −22.71 to −6.09; p = 0.0007), and elevated HDL-C (MD, 7.60; 95% CI, 4.33 to 10.87; p < 0.00001). Moreover, RYR effectively synergized nutraceutical to further reduce TC (MD, −31.10; 95% CI, −38.83 to −23.36; p < 0.00001), LDL-C (MD, −27.91; 95% CI, −36.58 to −19.24; p < 0.00001), and TG (MD, −26.32; 95% CI, −34.05 to −18.59; p < 0.00001). Additionally, RYR significantly reduced apoB (MD, −27.98; 95% CI, −35.51 to −20.45; p < 0.00001) and, whether alone or in combination, did not increase the risk of adverse events in patients with hyperlipidemia. Conclusion: RYR at 200–4800 mg daily appears to be a safe and effective treatment for hyperlipidemia, effectively regulating blood lipid levels with an exceptional impact on TG. Looking forward, high-quality clinical trials with longer observation periods are required to evaluate the efficacy and safety of RYR as a long-term medication. Systematic Review Registration: (https://www.crd.york.ac.uk/PROSPERO/), identifier (CRD4202128450).